Simply Speaking? Language Complexity among (Non-)Populist Actors in Parliamentary Debates - Rebecca C. Kittel (Government and Opposition, 2025)
Do populist politicians use simpler language to get closer to `ordinary' citizens? Current studies – both qualitative and quantitative – are divided on whether populist actors actually use simpler language. Analysing a large corpus of text of German parliamentary debates from January 1991 to September 2021, this article aims to resolve this controversy by measuring language complexity in parliamentary discourse. The article hypothesizes that populist actors use simpler language, following their ideal of a simplified world between `good' and `evil'. The analysis, however, positively refutes that, and instead shows that right-wing populist actors use the most complex language. Left-wing populists seem to use somewhat average language complexity. At the same time, the study finds that language complexity decreased significantly in the German parliament over time. Additionally, this article shows that language complexity is context-specific and people-dependent. As such, this article also discusses simple language as a tool for substantive and surrogate representation.
Keywords: 300; populism; language complexity; parliamentary debates; language style